Decision Support System Using The Ahp Method To Measure The Level Of Passenger Satisfaction At The International Terminal Of Tanjung Balai Asahan Port - Solider, Mariaman; Putri, Nadya Andhika (Bahasa Indonesia, 2024)
The Decision Support System (DSS) with the Analytical Hierarchy Process (AHP) method is an effective approach for measuring the level of passenger satisfaction at the Tanjung Balai Asahan Port International Terminal. The AHP method helps in identifying and evaluating various factors that influence passenger satisfaction, such as facilities, security, cleanliness, and service efficiency. By using AHP, the priority ranking of these criteria can be carried out based on opinions and assessments from passengers. It is hoped that the results of this SPK can provide valuable input for terminal managers to improve service quality, to create a more satisfying experience for passengers. This research discusses a decision support system that uses the Analytical Hierarchical Process (AHP) method to assess the level of passenger satisfaction at the Tanjung Balai Asahan Port International Terminal. Passenger satisfaction is a crucial factor in terminal operations, and measuring passenger satisfaction requires a systematic approach. This research conducted a direct survey of passengers with questions regarding their experiences while using transportation services. This survey can be carried out through interviews, and questionnaires. In this research, a scale or index is used to measure customer satisfaction. This index can combine various factors such as service, facilities, timeliness, and comfort. On operational data such as timeliness, number of complaints, level of delays, and incidents. This data can provide an indirect picture of passenger satisfaction.